Temperature and daily emergence of seven genera of Ephemeroptera (Insecta) in a cloud forest stream of tropical Andes - Chacón, María M. (2016)
Daily emergence of mayflies in Neotropical rivers and their causes have been poorly studied. In temperate zones, this process is better known and attributed to several factors. In this work, we studied the daily emergence of subimagines of several Ephemeroptera genera in La Picón River of a Venezuelan Andean cloud forest and its relation with changes of environmental temperature. Four emergence traps were placed along a reach of 50 m of the stream, each one was examined each two hours in a 24 hr cycle to capture the newly emerged subimagos. This procedure was repeated for eight dates between November-2007 and February-2008 for a total of 32 observations in each sampling hour. The subimagos were reared to adults and identified to genus. The relative density of emergence per trap was calculated for each genus and sampling hour. Water and air temperature were measured each hour during the daily cycle of observation, and the averages of temperature and hour-degrees of air and water were calculated for each hour from the eight dates studied. Seven genera were identified: Leptohyphes Eaton, 1882 and Haplohyphes Allen 1966 (Leptophlebiidae); Prebaetodes Lugo-Ortiz and McCafferty, 1996, Andesiops Lugo-Ortiz and McCafferty, 1999, Baetodes Needham and Murphy, 1924 and Americabaetis Kluge, 1992 (Baetidae); and Thraulodes Ulmer, 1920 (Leptophlebiidae); being the more abundant Leptohyphes (38.4 %) and Thraulodes (20.5 %). The emergence occurred between 11:00 am and 23:00 pm showing the following: a) an emergence initiated during daylight hours by organisms of Leptohyphes, Prebaetodes and Haplohyphes; b) a nocturnal emergence, in Thraulodes, Andesiops, Baetodes and Americabaetis; and c) two peaks: one diurnal produced by Leptohyphes and other nocturnal with predominance of Thraulodes. These results are the first records on the diurnal daily emergence in Andesiops, Prebaetodes, Americabaetis, Haplohyphes, and Leptohyphes, as well as the nocturnal emergence in Thraulodes. It was evidenced that Leptohyphes, with small nymphs (average head width = 1.05 mm) needed to accumulate less hour-degrees to initiate the emergence than those required by Thraulodes whose nymphs are larger (average head width = 2.01 mm). This disparity in the emergence energy requirements must be consequence of differences between the sizes of mature nymphs of both genera; facts which rely on the constancy of sizes shown by these taxa along an altitudinal-thermal gradient and the little daily and seasonal variability of water temperature in La Picón River. In the daily lapse when the emergence occurred, the air and water average temperatures were higher than those registered in the no-emergence lapse; therefore; it is suggested that during the daily lapse, when this process occurs, the environment is thermally favorable for the emergence of subimagos and their survival out of water.